Molecular scale bioelectrochemistry - Patil, A; Davis, J (2011)
Our ability to interface with biological macromolecules continues to advance at a significant pace and brings with it potential applications that are as broad as they are powerful. Running alongside this evolution has been the refinement of methods by which interfaces can be probed at scales approaching (or being at) the molecular. Through combinations of experimental design, proximal probe technology and high sensitivity optical imaging, one can truly probe the bioelectronic interface at levels that are both startling and associated with unprecedented levels of detail. © 2011 Elsevier B.V.